Coronaviruses in rodents and insectivores in Altai Republic - L. N. Yashina; S. A. Abramov; N. A. Smetannikova; B. S. Malyshev; A. V. Krivopalov; T. A. Dupal (Acta Biomedica Scientifica, 2024)
Coronaviruses (family Coronaviridae, genera Alphacoronavirus, Betacoronavirus) are dangerous viral pathogens that have caused three outbreaks of severe respiratory diseases, SARS, MERS, COVID-19. In Russia, data on coronaviruses in natural reservoirs are limited, as investigations began only during the COVID-19 pandemic.The aim. To study the diversity of coronaviruses among rodents and insectivores in the Republic of Altai.Materials and methods. Rodents (n  =  67) and shrews (n  =  52) were captured in 2022. Samples were analyzed by reverse transcription-polymerase chain reaction followed by sequencing.Results and conclusions. Four samples from rodents (Myodes rutilus, M. glareolus, Apodemus peninsulae, A. agrarius) and two samples from an insectivore (Crocidura sibirica) were positive for coronaviruses, among which three different coronaviruses were detected. Rodent-borne coronaviruses are classified in the genus Betacoronavirus, subgenera Embecovirus, and have shown host associated clustering. The nucleotide sequences of Siberian coronaviruses from rodents were identical for closely related species (M. rutilus and M. glareolus, A. agrarius and A. peninsulae) and close (> 94 % homology) to previously published sequences in each of the groups of carriers found in the territory Novosibirsk region, Europe and China. The coronavirus identified from the insectivore, possibly belonging to a new subgenera of the family Coronaviridae, has also been assigned to the genus Betacoronavirus.Conclusion. Five species of natural carriers of three different coronaviruses were detected in the Altai Republic. A high level of identity of coronaviruses genomes from rodents has been revealed, indicating a relatively low rate of their evolution.